Steadiness of syllable repetition in early motor stages of Parkinson's disease. (March 2015) - Skodda, Sabine
Highlights: Steadiness of syllable repetition was found to be impaired in speakers with early motor Parkinson's disease (PD). Maximum velocity of syllable repetition was similar in patients with PD and healthy control speakers. Abnormal patterns of basic motor speech performance could discriminate PD speakers from healthy controls. Measurement of syllable repetition capacity could help to detect subtle abnormalities of basic motor speech performance in early stage PD. Abstract: Patients with Parkinson's disease (PD) show characteristic abnormalities in the performance of simple repetitive movements which can also be observed concerning speech rate and rhythm. The aim of the current study was to survey if patients with early PD already feature impairments of steady vocal pace performance based upon a simple syllable repetition paradigm. N  = 50 patients with PD with mild to moderate motor impairment and n  = 32 age-matched healthy controls were tested. Participants had to repeat a single syllable or a pair of alternating syllables in a self chosen steady pace or in a given pace of 80/min. The coefficient of variance was taken as measure of stability of repetition. As main and novel result, vocal pace performance was observed to be irregular in all patients, even in the subgroup of PD patients with only very mild motor impairment (Hoehn&Yahr stage 1), although the capacity of rapid syllable repetition was preserved. Weak correlations were found between the maximum repetition rate (but not with steadiness of repetition) and some distinctive Parkinsonian motor features as speech impairment and gait. Assumed that subsequent studies are able to confirm these preliminary results, analysis of steadiness of syllable repetition might be a promising non-invasive tool for detection of subtle abnormalities of motor speech performance even in the early motor stages of PD.